1992
DOI: 10.3109/10715769209083143
|View full text |Cite
|
Sign up to set email alerts
|

Possible Reasons for Differences in Phototoxic Potential of 5 Quinolone Antibacterial Agents: Generation of Toxic Oxygen

Abstract: The reason for the differences in phototoxic potential between the 5 quinolone antibacterial agents lomefloxacin, enoxacin, ciprofloxacin, ofloxacin and DR-3355 (the s-isomer of ofloxacin) in mice was investigated. Superoxide anion, hydrogen peroxide (H2O2), and bleaching of p-nitrosodimethylaniline (B-NDMA) were detected in quinolone solutions during irradiation with ultraviolet-A (UVA). Apparent levels of H2O2 and the B-NDMA per mole of quinolone paralled the phototoxic potentials in the mice. The N-NDMA ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…Furthermore, a-tocopherol acetate supplementation reduced enrofloxacin residues in turkey meat, which indicate a possible interaction between both molecules that reduces the amount of enrofloxacin in tissues [4,25]. Studies on phototoxic actions of fluoroquinolones revealed that these toxic effects are related to induction of reactive oxygen species [12,23,[27][28][29][30].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, a-tocopherol acetate supplementation reduced enrofloxacin residues in turkey meat, which indicate a possible interaction between both molecules that reduces the amount of enrofloxacin in tissues [4,25]. Studies on phototoxic actions of fluoroquinolones revealed that these toxic effects are related to induction of reactive oxygen species [12,23,[27][28][29][30].…”
Section: Discussionmentioning
confidence: 96%
“…55,56 Phototoxicity Phototoxicity is a potential risk with all contemporary fluoroquinolones, 55 notably those with multiple fluorine side-chain substitution (fleroxacin, sparfloxacin) and those with a chlorine substituent at the 8-position (clinafloxacin, Bay y 3118). 61 In contrast, levofloxacin (1,8 cyclic) and the 8-methoxyquinolones pose minimal risk, [62][63][64][65] probably related to their differentially lesser ability to generate free oxygen radicals in the skin. 64 For these latter agents, phototoxicity, which amounts to no more than mild sunburn, occurs in Ͻ0.05% of patients.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…61 In contrast, levofloxacin (1,8 cyclic) and the 8-methoxyquinolones pose minimal risk, [62][63][64][65] probably related to their differentially lesser ability to generate free oxygen radicals in the skin. 64 For these latter agents, phototoxicity, which amounts to no more than mild sunburn, occurs in Ͻ0.05% of patients. 55,56 QT Interval Prolongation and Ventricular Arrhythmia Prolongation of the QTc by fluoroquinolones and their potential for precipitation of ventricular arrhythmia is a concern.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…UVA ışınıyla oluşturulmuş irritasyon indeksi -ışınlama olmayan irritasyon indeksi (39) 0.6 indeks değeri üzerindeki değerler potansiyel fototoksisiteyi gösterir.…”
Section: In Vivo Fototoksisite Testleriunclassified